Effect of host shift on the gut microbes of Bactrocera cucurbitae (Coquillett) (Diptera: Tephritidae) - Tian, Zhenya; Chen, Lixiang; Chen, Guangmei; Wang, Jingjing; Ma, Chao; Zhang, Yan; Gao, Xuyuan; Chen, Hongsong; Zhou, Zhongshi (Frontiers in Microbiology, 2023)
To understand the role of gut microbes in insect adaptation, it is necessary to study the dynamics of insect gut microorganisms during host transfer. Using Bactrocera cucurbitae (Coquillett) (Diptera: Tephritidae) and its four hosts as study subjects, we investigated the dynamics of gut microbes during host transfer and the effects of different hosts on the gut microbial composition of B. cucurbitae. The results showed that the Chao1 index of B. cucurbitae decreased significantly during host transfer, and the intestinal microorganisms were significantly affected by the original host, host, and generations. Furthermore, predicated changes in the abundance of secondary metabolite pathways after host transfer suggested that microorganisms may play an important role in the degradation of secondary metabolites, among which Providencia and Morganella have important functions in the gut of B. cucurbitae. This implied that microorganisms play a function in the host transfer process of B. cucurbitae and may be an important cofactor in the adaptation of B. cucurbitae to different hosts and environments, providing new research ideas for the future control of B. cucurbitae.